Peran Pejabat Pembuat Akta Tanah Dalam Pendaftaran Tanah Sistem Lengkap - Mohammad Firza Rokhmansyah; Nynda Fatmawati Octarina (Law Department, Sharia and Law Faculty., 2022)
A lack of understanding of the importance of land registration for the first time that was issued, lead to a limited ownership of the land certificate of rights. Until now, the land owned by the society are largely uncertified. This study aims to know and analyze the role of the Land Deed Official in the performance of land registration, and also to analyze the importance of land registration in assigning legal theories of certainty. The research method uses empirical juridical, with a sociological juridical approach. The location of the research conducts in the National Land Agency of Kabupaten Mojokerto, using the primary and secondary types of data. The data analysis is qualitative. In the first phase of land registration, the roles of the Land Deed Official are particularly important when it comes to legal transitions of land rights, the imposition of land rights which are used as the basis for land rights registration. In the perspective of a legal certainty theory, listing land is essential in order to obtain legal certainty over land ownership. The land that has been listed will avoid any act of arbitrariness.Kata Kunci: Registration, Land, Legal Certainty.